DEFICIENCIES IN THE USE OF SOCIAL FOOD ASSISTANCE FUNDS (SEMBAKO PROGRAM) WITH A PACKAGE SYSTEM FOR POOR FAMILIES - DEDIK - HARIANTO (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2022)
National development is intended to achieve dynamic social change in the form of meeting the basic needs of society. The process of social change increases the standard of living of the poor as a whole, where development is carried out to complement each other through the process of economic development. However, if this change process does not go according to plan, it shows an indication of a deficiency in the program. Government assistance such as the Food Social Assistance (Sembako Program) is one form of social protection effort to reduce the expenditure burden of poor and vulnerable families in meeting their food needs. The efficient use of grants is also the key to the success of the development process itself. Herein lies the important role of the structural functions of each agent such as the Social Service as a local policy maker, the State Bank Association (Himbara) as a distributor of funds, a Supplier as a supplier of foodstuffs, an Agent / E-Warong as a food seller and a Beneficiary Family (KPM) as a fund manager. If their respective roles are not in accordance with the main policies of the program makers, this shows that there is a deficiency in the use of grants that are not in accordance with general guidelines.Keywords: Poverty, Food Social Assistance, Structural-Functional